Retroperitoneoscopic Upper Pole Nephroureterectomy in Duplex Kidney:Focus on the Role of Dilated Upper Pole Ureter - Chen, Zhi; Tang, Zheng-Yan; Fan, Ben-Yi; Chen, Xiang; Zhou, Peng; Luo, Yan-Cheng; He, Yao; Xie, Chao-Qun; Lai, Chen; Fang, Xiao-Long (Urology Journal, 2014)
Abstract Purpose: To describe our technique and experience with retroperitoneoscopic upper pole nephroureterectomy in duplex kidney, focusing on the role of dilated upper ureter. Materials and Methods: From November 2004 to August 2011, retroperitoneoscopic upper pole nephroureterectomy was performed in 31 patients with a duplex kidney by a single, experienced laparoscopic surgeon. We developed our own surgical technique to suit this technically challenging procedure. Follow-up studies were performed using renal ultrasonography, intravenous urography (IVU) and/or dimercaptosuccinic acid (DMSA) renal scan in all patients at 3 months postoperatively and annually thereafter. Results: All procedures were completed laparoscopically without conversion to open surgery and blood transfusion. The mean operative time was 106 (90-157) min. The estimated blood loss was < 50 mL in all cases. The mean postoperative hospital stay was 4.2 (3-7) days. Perioperative complications were limited to 1 case of peritoneal tear during a procedure and 1 case of transient postoperative fever. No major intraoperative and postoperative complication occurred. With the mean follow-up period of 41 months (range 3 to 80), no case was observed to have functional loss of the remaining lower moiety on postoperative IVU or DMSA renal scan. Conclusion: Retroperitoneoscopic upper pole nephroureterectomy using our technique is safe and effective.